42‐4: LTPS TFT‐LCD with In‐cell Optical Fingerprint Scanner. Issue 1 (25th September 2020) - Liu, Bozhi; Chen, Binbin; Wu, Xiaoxiao; Cai, Xuanxian; Shi, Xiaoqi; Huang, Min; Wu, Jiaqian; Wang, Hailiang; Lan, Xuexin; Chen, Guozhao; Li, Junyi
Abstract : LTPS image sensor (LIS) driven by active pixel senor (APS) circuit based on LTPS backplane technology is demonstrated. Optical solution for LCD with in‐cell optical fingerprint scanning function is discussed. A 400PPI LTPS‐TFT LCD with in‐cell touch and in‐cell screen fingerprint scanning function is designed to realize fingerprint image capture when finger is 1.0mm height over the LIS array.